Analisis Debit Banjir Sungai Krueng Baro Kabupaten Pidie - Syahputra, Ichsan; Irfan, Zu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Krueng Baro River in Pidie Regency has a total length of ± 143.50 Km and a total Watershed Area (DAS) of ± 378.21 Km2. At the flood review point at the Krueng Baro Bridge, the watershed area is ± 237.42 Km2. Daily maximum annual rainfall data was collected from 2014 to 2024 from the BPP Tangse, BPP Mutiara, and BPP Keumala stations. The annual maximum daily rainfall ranged from 92 mm (2021) to 178 mm (2017). The hydrological modeling was conducted using the HEC-HMS application, while the river modeling used HEC-RAS. The hydrological statistical analysis, using various distribution methods (Gumbel, Normal, Log Normal, Log Pearson type III), predicted the recurrence period rainfall. The TR-100 (100-year recurrence period) rainfall is estimated at 270.32 mm. The TR-100 flood discharge at the Krueng Baro Bridge is 533.43 m3/sec. Despite this significant discharge, the floodwater level is at an elevation of +8.21 m. The ground elevation around the bridge is at +9.87 m (right) and +9.30 m (left). Since the floodwater elevation (+8.21 m) is lower than the ground elevation on both sides of the river, the water will not overflow and will not reach the floor of the existing Krueng Baro Bridge. This indicates that the current bridge is safe from a 100-year recurrence flood event.